Effect of rice husk particle size on ZSM-5 physico-chemical properties for selective formation of 1,3,5-trimethyl-2-benzylbenzene (Pharmaceutical Intermediate) - Ghuge, Gorakh; Niphadkar, Prashant; Rathod, Simmy; Bokade, Vijay V. (ChemistrySelect, 2021)
Rice husk, rich in silica and abundantly available as waste, is presently destroyed by burning, which creates environmental issues. Thus, it will be advantageous if this rice husk waste can be used for preparation of valuable products. One of the application is its use as silica source in the synthesis of zeolites like ZSM-5, which are silico-aluminates. Rice husk waste is available in wide range of particle sizes in agricultural farms. There is no study available in open literature on use of these wide particle ranges for its direct application. This paper is an attempt to use wide particle size rice husk, its effect on ZSM-5 synthesis and its physico-chemical properties. Further these prepared ZSM-5 catalyst was evaluated for benzylation of mesitylene reaction. The study found that, rice husk of 600 mu m particle size is optimum as far as ZSM-5 synthesis, its physicochemical properties and further its application in mesitylene benzylation reaction.
Keywords: Mesitylene; Particle size; rice husk; Silica Source; ZSM-5